The Use of Recycled Educational Tools to Develop Emotional Competence in Early Childhood: A Case Study at TK Tunas Harapan Bangsa, PTPN IV REG 4, Muhajirin Village - Rohani Rohani; Achmad Fadlan; Jamilah Jamilah (Darul Yasin Al Sys, 2026)
Emotional development is a fundamental aspect of early childhood education that should be nurtured through engaging, meaningful, and contextually relevant learning activities. However, the use of learning media that optimally stimulate children’s emotional development, particularly by utilizing resources from the surrounding environment, remains limited. This study aims to describe the use of recycled educational materials in fostering young children’s emotional development at Tunas Harapan Bangsa PTPN IV Reg IV Kindergarten in Muhajirin Village. This study employed a qualitative approach with a descriptive research design. The research subjects comprised the principal, classroom teachers, young children, and parents as supporting informants, selected through purposive sampling. Data were collected through observation, interviews, and documentation and analyzed using an interactive model consisting of data reduction, data presentation, and conclusion drawing. Data validity was ensured through source, technique, and temporal triangulation. The findings indicate that recycled educational tools made from natural materials available in the surrounding environment can create enjoyable and meaningful learning experiences for children. Activities such as collage-making and other creative projects supported emotional development, as reflected in increased self-confidence, cooperation, patience, emotional self-regulation, responsibility, and empathy toward peers. This study concludes that recycled educational materials can function as effective, economical, and contextually relevant learning media for supporting emotional development in early childhood. The findings contribute to early childhood education by demonstrating how environmentally based learning media can simultaneously foster emotional competence and cultivate environmental awareness from an early age.